Sleep Characteristics and Measures of Glucose Metabolism in Blacks: The Jackson Heart Study. Issue 9 (5th May 2020) - Yano, Yuichiro; Gao, Yan; Johnson, Dayna A.; Carnethon, Mercedes; Correa, Adolfo; Mittleman, Murray A.; Sims, Mario; Mostofsky, Elizabeth; Wilson, James G.; Redline, Susan
Abstract : Background: Characterizing associations of sleep characteristics with blood‐glucose–level factors among blacks may clarify the underlying mechanisms of impaired glucose metabolism and help identify treatment targets to prevent diabetes mellitus in blacks. Methods and Results: Cross‐sectional analyses were conducted in 789 blacks who completed home sleep apnea testing and 7‐day wrist actigraphy in 2012–2016. Sleep‐disordered breathing measurements included respiratory event index associated with 4% oxygen desaturation and minimum oxygen saturation. Sleep patterns on actigraphy included fragmented sleep indices. Associations between sleep characteristics (8 exposures) and measures of glucose metabolism (3 outcomes) were determined using multivariable linear regression. Mean (SD) age of the participants was 63 (11) years; 581 (74%) were women; 198 (25%) were diabetes mellitus, and 158 (20%) were taking antihyperglycemic medication. After multivariable adjustment, including antihyperglycemic medication use, the betas (95% CI) for fasting glucose and hemoglobin A1c, respectively, for each SD higher level were 0.13 (0.02, 0.24) mmol/L and 1.11 (0.42, 1.79) mmol/mol for respiratory event index associated with 4% oxygen desaturation and 0.16 (0.05, 0.27) mmol/L and 0.77 (0.10, 1.43) mmol/mol for fragmented sleep indices. Among 589 participants without diabetes mellitus, the betas (95% CI) for homeostatic model assessment of insulin resistance for each SD higher level were 1.09 (1.03, 1.16) for respiratory event index associated with 4% oxygen desaturation, 0.90 (0.85, 0.96) for minimum oxygen saturation, and 1.07 (1.01, 1.13) for fragmented sleep indices. Conclusions: Sleep‐disordered breathing, overnight hypoxemia, and sleep fragmentation were associated with higher blood glucose levels among blacks.